Organizational and economic aspects of residential buildings renovation with decorative elements on the roof - T. E. Gordeeva; O. A. Mamaeva (Vestnik MGSU)
Introduction. The problem of preservation of decorative elements on the roofs of multi-apartment residential buildings is considered. The authors note the historical and architectural value of such structures in creating the appearance of the city. An analysis of the current technical condition of decorative elements of roofs is carried out using the example of individual apartment buildings in Samara and, based on a comprehensive analysis, recommendations are given for their further operation. The problematics is investigated by the authors using the example of Samara city and, accordingly, are based on the practical basis of this city. At the same time, the questions and proposals posed in the paper are relevant and can be extended to the residential development of most Russian cities. This is due to the fact that the organizational and legal field of this problem is established at the level of federal legislation, and in the regions it develops only in the form of not the most significant features.Materials and methods. When developing the present problem, the authors used a set of generally accepted research methods — observation, comparison, measurement, abstraction — in adaptation to the object and subject of research. The research is based on the materials and results of the author’s own research in relation to technical, cost and regulatory parameters of the repair of decorative elements of flat roofs of multi-apartment high-rise buildings, made according to a standard and individual project in Samara city.Results. The regulatory and legal framework in force in relation to the overhaul of the common property of an apartment building is analyzed. Defects and problems were identified — corrosion of metal structures, destruction of wooden elements. The impact of dismantling of structures on the appearance of buildings is assessed. A comparative assessment of the cost of repair and restoration of roof elements is given. The current regulatory framework for overhaul in apartment buildings is analyzed. It is noted that there is no clear regulation of financing the repair of the roof structures under consideration. The estimated cost of overhaul of additional roof elements is determined according to alternative options for its production. The conclusion is made about the need for an integrated approach, taking into account the technical condition, financial capabilities and legal regulation to solve the identified problem.Conclusions. Proposals are made to improve the normative-methodical and normative-technical mechanisms to ensure the safety of historically and architecturally valuable elements of roofs and the safe operation of apartment buildings in Samara.